Technology of managerial competence formation of future managers of physical culture - Oleksandr Aghyppo; Maryna Korolova (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to develop and theoretically substantiate the technology of forming the managerial competence of future managers of physical culture. Material and methods: a theoretical analysis of modern literature on the problem under the study was carried out; the regulatory framework for the training future managers of physical culture is analyzed; a survey of applicants for education of the second (master's) level of higher education was conducted (n = 50); using the method of paired comparison, an expert assessment among the teaching staff of the Kharkov State Academy of Physical Culture (n = 10) was carried out. Results: the concepts of "competence", "competency", "managerial competence", "managerial competency" were clarified; self-assessment was revealed and self-analysis of applicants for education of the second (master's) level of higher education of learning outcomes in terms of the level of formation of their managerial competencies was carried out; the most significant managerial competencies of the future managers of physical culture were determined. Based on the results of our own research, the matrix of managerial competence of a physical culture manager is presented. The technology has been developed and substantiated: methods, forms and means of forming managerial competence among future managers of physical culture. Conclusions: management competencies have been identified, which are important for the implementation of the future management activities of physical culture managers, among them the first five positions are occupied by: leadership, idea generation, communication, mastery of the system for solving managerial problems and business qualities.